Higher Performance of QuantiFERON TB Compared to Tuberculin Skin Test in Latent Tuberculosis Infection Prospective Diagnosis - Dhaouadi, Tarak; Sfar, Imen; Mouelhi, Leila; Tekaya, Raoudha; Mahmoud, Ines; Bargaoui, Jalila; Daghbouj, Raoudha; Abdelmoula, Leila; Najjar, Taoufik; Abdallah, Taieb Ben; Gorgi, Yousr (International Journal of Statistics in Medical Research, 2016)
Background: The Tuberculin skin test (TST) has been used for years in the latent tuberculosis infection (LTBI) diagnosis, but it has, well-documented, low sensitivity and specificity. Interferon-γ release assays (IGRA) has been reported to be more sensitive and specific than TST. Therefore, this study aimed to evaluate the performance of a commercial IGRA, QuantiFERON®-TB Gold In-Tube (QFT-GIT), comparatively to TST in LTBI diagnosis. Patients and Methods: This study included 238 patients who were candidate for an anti-TNF therapy. The screening for LTBI was performed by both TST and QFT-GIT test for all patients. In order to evaluate the strength of associations, the odds ratios (OR) together with 95% confidence intervals (CI) were calculated. The correlation between QFT-GIT and TST was evaluated using κ statistics. Results: Sixty-three (26.4%) sera were positive for QFT-GIT with a mean level of IFN-γ of about 1.18 IU/ml, while 81 (34%) patients were positive for TST. Agreement between QFT-GIT and TST was poor (37 QFT-GIT+/TST- and 55 QFT-GIT-/TST+), κ=0.09 (SD=0.065). The positivity of QFT-GIT was not influenced by BCG vaccination or by immunosuppression. Nevertheless, it was significantly associated to both history of an earlier tuberculosis disease (HETD) and its radiological sequel (RS), p=6E-7 and p=1E-8, respectively. Inversely, the TST results were not correlated to either HETD or RS, but the TST positivity was less frequent in immunosuppressed patients (45.5% vs. 73.9%), p=1E-5, OR (95% CI) = 0.29 [0.17-0.52]. Moreover, the extent of both the immunosuppression period and the time elapsed from the last BCG injection was significantly correlated to a lesser TST positivity, p=3E-12 and p=5E-7, respectively. Among the QFT-GIT-/TST+ patients (n=55) whom received an anti-TNF agent without any prophylactic treatment of LTBI, no tuberculosis was detected with a median follow-up of 78 weeks [56-109]. Conclusion: Our study suggests that the QFT-GIT has a higher performance comparatively to TST in the LTBI screening that is unaffected by either BCG vaccination or immunosuppression. Therefore, IGRAs has to replace TST especially in patients who are under consideration for an anti-TNF therapy.